Progestin-primed ovarian stimulation outcomes in in-vitro fertilization (IVF) - A systematic review of the literature - Vyacheslav Notanovich Lokshin; Aigerim Temirkhanovna Abshekenova; Gian Carlo Di Renzo; Michael Feichtinger; Sholpan Kenesovna Karibayeva; Dana Margulanovna Syzdykova (Taylor & Francis Group, 2024)
Background: Progestin-primed ovarian stimulation (PPOS) stimulates ovaries to block the premature surge of luteinizing hormone (LH) by using micronized progesterone or a progestin during the follicular phase instead of the conventional gonadotropin-releasing hormone (GnRH) analogues or GnRH antagonists downregulating LH to obtain multi-follicle engagement. Current work aims to assess the influence of progestogen treatment on ovarian stimulation and the ability to control LH surge, its efficacy and suitability in retrieving oocytes, without affecting the embryo quality and its benefit among infertile women long-term outcomes on children compared to standard stimulation protocols. Materials and Methods: The literature review used the randomized control trials published in the Pubmed database from January 2015 to April 2021. To generate the citation list, the following keywords were used: 'progestin-primed ovarian stimulation', 'PPOS', 'micronized progesterone', 'medroxyprogesterone', and/or 'dydrogesterone'. The selected articles analyzed the cohort, intervention, and scheme of the progestin-primed ovarian stimulation protocol in controlled ovarian stimulation (COS) for in-vitro fertilization (IVF)/intra cytoplasmic sperm injection (ICSI) used in Assisted Reproductive Technologies (ART). Results: Overall we concluded that PPOS for IVF/ICSI in ART results in a higher number of obtained embryos, lower incidence of OHSS, equal duration of stimulation, number of retrieved oocytes, and number of MII oocytes. It is also suggested that long-term safety in children shows no significant difference between the study and control groups. Conclusions: Despite the outcomes of progestin stimulation cycles among all cohorts, we concluded that poor ovarian responders, patients with PCOS, women of advanced age and oocyte donors benefit the most from using PPOS.